Hypocretin 1/orexin A in the ventral tegmental area enhances dopamine responses to cocaine and promotes cocaine self-administration - España, Rodrigo A. (2010)
RATIONALE: Recent evidence indicates that the hypocretin/orexin system participates in the regulation of reinforcement and addiction processes. For example, manipulations that decrease hypocretin neurotransmission result in disruptions of neurochemical and behavioral responses to cocaine. OBJECTIVES: To further assess the relationship between the hypocretin system and cocaine reinforcement, the current studies used microdialysis and in vivo voltammetry to examine the effects of hypocretin 1 on cocaine-induced enhancement of dopamine signaling in the nucleus accumbens core. Fixed ratio, discrete trials, and progressive ratio self-administration procedures were also used to assess whether hypocretin 1 promotes cocaine self-administration behavior. RESULTS: Infusions of hypocretin 1 into the ventral tegmental area increased the effects of cocaine on tonic and phasic dopamine signaling and increased the motivation to self-administer cocaine on the discrete trials and progressive ratio schedules. CONCLUSIONS: Together with previous observations demonstrating that a hypocretin 1 receptor antagonist disrupts dopamine signaling and reduces self-administration of cocaine, the current observations further indicate that the hypocretin system participates in reinforcement processes likely through modulation of the mesolimbic dopamine system.